From Noisy Data to Feedback Controllers: Nonconservative Design via a Matrix S-Lemma - van Waarde, Henk J.; Camlibel, M. Kanat; Mesbahi, Mehran (IEEE transactions on automatic control, 2022)
In this article, we propose a new method to obtain feedback controllers of an unknown dynamical system directly from noisy input/state data. The key ingredient of our design is a new matrix S-lemma that will be proven in this article. We provide both strict and nonstrict versions of this S-lemma, which are of interest in their own right. Thereafter, we will apply these results to data-driven control. In particular, we will derive nonconservative design methods for quadratic stabilization, \mathcal {H}_2 and \mathcal {H}_{∞ } control, all in terms of data-based linear matrix inequalities. In contrast to previous work, the dimensions of our decision variables are independent of the time horizon of the experiment. Our approach, thus, enables control design from large datasets.